Bone defect repair material and preparation method and use thereof
By using polylactic acid-glycolic acid copolymer and calcium phosphate materials, combined with FDM high-temperature melting 3D printing technology, the problem of high processing cost and low accuracy of bone defect repair materials is solved, and low cost and high precision preparation of bone defect repair materials is achieved, with good mechanical and biocompatibility.
Patent Information
- Application Number
- CN202310068765.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-02-06
AI Technical Summary
Existing bone defect repair materials have shortcomings in the problems of high processing costs, low accuracy and difficulty in ensuring the precise design and manufacturing of micropore structures.
Polylactic acid-glycolic acid copolymer and calcium phosphate materials are used as raw materials to prepare bone defect repair materials through FDM high-temperature melting 3D printing technology to ensure that the material is easy to obtain, the processing cost is low and the accuracy is high.
It realizes the low-cost and high-precision preparation of bone defect repair materials, has bone conductivity, osteoinduction, biocompatibility and biodegradation capabilities, provides effective mechanical support, and can be personalized according to the appearance of the bone defect site.
Smart Images

Figure CN116350851B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bone repair materials, and in particular relates to a bone defect repair material and a preparation method and application thereof. Background Art
[0002] In clinical practice, bone defects caused by bone and joint infection, tuberculosis or tumor erosion, severe trauma, etc. are relatively common, and the repair of large bone defects has become one of the most difficult problems in the field of orthopedics. At present, the method for repairing large bone defects is bone grafting, and the commonly used sources of grafts include autologous bone, allogeneic bone, xenogeneic bone and various inactive artificial bones. However, autologous bone transplantation has defects such as limited sources of autologous bone and complications such as infection at the bone harvesting site; allogeneic bone and xenogeneic bone are easy to spread infectious diseases, and more importantly, they can cause immune rejection. The artificial bone transplantation substitute materials such as scaffold metal produced by the currently commonly used traditional process methods are only simple artificial substitute materials, which have the problem of difficult degradation or the degradation rate is inconsistent with the bone growth rate, affecting osteogenesis or body function, and cannot guarantee the precise design and manufacturing of microporous structures, let alone the combination and assembly of different materials, and there is a clinical problem of difficulty in removal. For a long time, researchers have been committed to the development of artificial bone transplant substitutes. Polymer materials have sufficient mechanical properties and are suitable for the repair of critical bone defects. Polylactic acid (PLA) has been defined as a biomaterial with potential clinical application value in many studies due to its slow degradation performance and reliable biocompatibility.
[0003] However, pure polymer scaffolds lack osteoinductive function, and components with osteoinductive function need to be introduced. Tricalcium phosphate (TCP) is an absorbable bone repair material that is easily replaced by new bone. Its solubility is close to that of bone mineral, so TCP does not dissolve under physiological conditions, but can be absorbed by cells (usually osteoclasts) (cells cause local acidification leading to β-TCP dissolution). TCP has a high osteoinductive ability and can promote the differentiation of stem cells. Xu Gang et al. (Chinese Journal of Aesthetic Medicine, Vol. 30, No. 5, May 2021, pp. 59-62) reported a composite vancomycin / PLGA / TCP bone defect repair scaffold material prepared by low-temperature 3D printing technology. The scaffold material has a high porosity and good interconnectivity. It has excellent performance in vancomycin sustained release ability and antibacterial effect. It can be regarded as a scaffold material with potential clinical application value, especially suitable for the repair of infected bone defects. However, the bone defect repair scaffold material has the following problems: 1) It is prepared using low-temperature 3D printing technology, and the processing cost of this method is relatively high; 2) The bone defect repair scaffold material prepared by this method has low precision, and it is difficult to ensure the accurate design and manufacturing of the microporous structure.
[0004] In order to solve the above problems, it is of great significance to develop a bone defect repair material with lower processing cost, higher precision and the ability to ensure the precise design and manufacturing of the microporous structure. Summary of the invention
[0005] The purpose of the present invention is to provide a bone defect repair material and a preparation method and use thereof.
[0006] The present invention provides a bone defect repair material, which is prepared by using polylactic acid-glycolic acid copolymer and calcium phosphate material as raw materials, wherein the mass ratio of the polylactic acid-glycolic acid copolymer to the calcium phosphate material is (5-7): (3-5).
[0007] Furthermore, the mass ratio of the polylactic acid-glycolic acid copolymer to the calcium phosphate material is 7:3.
[0008] Furthermore, in the polylactic acid-glycolic acid copolymer, the molar ratio of lactic acid to glycolic acid is (75-50):(25-50), preferably 50:50.
[0009] Furthermore, the calcium phosphate material is tricalcium phosphate, hydroxyapatite, tetracalcium phosphate or dicalcium phosphate.
[0010] Furthermore, the calcium phosphate material is tricalcium phosphate.
[0011] The present invention also provides a method for preparing the above-mentioned bone defect repair material, which comprises the following steps:
[0012] (1) adding calcium phosphate material into organic solvent 1 and dispersing the material evenly to obtain a suspension of calcium phosphate material;
[0013] (2) adding the polylactic acid-glycolic acid copolymer into the organic solvent 2 to dissolve the polylactic acid-glycolic acid copolymer to obtain a polylactic acid-glycolic acid copolymer solution;
[0014] (3) mixing the calcium phosphate material suspension and the polylactic acid-co-glycolic acid solution uniformly, removing the organic solvent, and drying to obtain a composite material;
[0015] (4) crushing and extruding the composite material, and collecting the wire;
[0016] (5) The wire is subjected to high-temperature melting 3D printing to obtain a bone defect repair material.
[0017] Furthermore, in step (1), the organic solvent 1 is acetone; in step (2), the organic solvent 2 is dichloromethane or chloroform;
[0018] In step (1), a dispersant is added to the organic solvent 1; the dispersant is preferably polyethylene glycol; the mass volume ratio of the calcium phosphate material to the dispersant is (20-30) g:1 ml, preferably 25 g:1 ml;
[0019] In step (5), the parameters of the high temperature melting 3D printing include: the thickness of each layer is 0.1-0.3 mm, preferably 0.2 mm; the printing speed is 50-70 mm / s, preferably 60 mm / s.
[0020] The present invention also provides an anti-infection bone defect repairing material, which is obtained by coating antibiotics on the above-mentioned bone defect repairing material.
[0021] Furthermore, the antibiotic is an aminoglycoside antibiotic, preferably gentamicin.
[0022] The present invention also provides uses of the above-mentioned bone defect repair material and the above-mentioned anti-infection bone defect repair material in preparing a bone defect repair scaffold.
[0023] The present invention has achieved the following beneficial effects:
[0024] 1. The present invention adopts FDM 3D printing technology to prepare bone defect repair scaffolds. The raw materials of the scaffolds are low-priced and easy to obtain, the processing method is low-cost, the processing method is simple, convenient, and easy to use in hospital scenarios, and the obtained bone defect repair scaffolds are of high precision, which can ensure the precise design and manufacturing of the microporous structure.
[0025] 2. The bone defect repair scaffold provided by the present invention has osteoconductivity, osteoinductivity, biocompatibility and biodegradability, and can also provide effective mechanical support.
[0026] 3. The bone defect repair scaffold provided by the present invention can be individually designed according to the scanning results of the shape of the bone defect site, and the pore size and pores can be accurately designed to achieve structural bionics, with wide and accurate adaptability.
[0027] 4. The surface of the bone defect repair scaffold provided by the present invention is uniformly distributed with TCP particles, which has a large surface area and is easy to absorb nutrients and drugs such as serum proteins.
[0028] 5. The anti-infection bone defect repair scaffold provided by the present invention contains a gentamicin coating, which can provide an antibacterial effect. The local use effect brought by the coating avoids the side effects of systemic medication.
[0029] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0030] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Physical pictures of the anti-infection bone defect repair scaffold prepared by the present invention (a, b); Physical picture of the composite vancomycin / PLGA / TCP bone defect repair scaffold material reported in the prior art (c).
[0032] Figure 2 : Scanning electron micrograph of the anti-infection bone defect repair scaffold prepared by the present invention (a); Scanning electron micrograph of the composite vancomycin / PLGA / TCP bone defect repair scaffold material reported in the prior art (b).
[0033] Figure 3 : After implanting rabbit bone defect mesenchymal stem cells in the anti-infection bone defect repair scaffold of the present invention, electron microscopy observation revealed that the cells spread normally on the surface of the scaffold, proving its good biocompatibility.
[0034] Figure 4 : The anti-infection bone defect repair scaffold of the present invention was implanted with rat mesenchymal stem cells and then subjected to live-dead staining, which proved its good biocompatibility. DETAILED DESCRIPTION
[0035] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0036] The specification of polylactic acid-glycolic acid copolymer (PLGA) is 50:50 (50:50 means the molar ratio of lactic acid to glycolic acid is 50:50); tricalcium phosphate (TCP).
[0037] Example 1: Preparation of bone defect repair scaffold
[0038] 1. Preparation of TCP Acetone Suspension
[0039] Nano-scale TCP powder (25 g) was added with 10 times the volume of acetone, and ultrasonicated at 600 W power, while stirring at medium speed of a cantilever stirrer for 4 h. Then polyethylene glycol 400 (1 ml) was added, and the mixture was transferred to a magnetic stirrer and stirred at medium speed overnight to obtain a TCP acetone suspension.
[0040] 2. Preparation of PLGA Solution
[0041] PLGA particles (PLGA specification is 50:50) were added to ten times the volume of chloroform to dissolve, and allowed to stand at 25° C. for 48 hours to obtain a PLGA solution.
[0042] 3. Material Composite
[0043] The TCP acetone suspension obtained in step 1 and the PLGA solution obtained in step 2 were mixed (the mass ratio of PLGA to TCP was controlled to be 7:3), ultrasonicated at 600 W power, and stirred at medium speed with a cantilever stirrer for 2 h. The mixture was poured into a glass dish with a diameter of 18 mm. After the organic solvent was evaporated in a chemical fume hood, the mixture was vacuum dried for 24 h to obtain a dry composite material.
[0044] 4. Preparation of wire
[0045] The dried composite material block was cut into pieces and placed into a pulverizer to obtain composite powder, which was then added into the extruder silo (the temperature was set at 160°C). The temperature of the extrusion head was set at 165°C. When the surface of the extruded wire was smooth and free of bubbles, the wire was collected.
[0046] 5. Printing processing
[0047] Draw a personalized 3D model according to the location of the bone defect, and put the filaments collected in the previous step into a fused deposition modeling (FDM) printer for high-temperature melting 3D printing to obtain a printed scaffold, i.e., a bone defect repair scaffold.
[0048] The parameters of high-temperature melting 3D printing were set as follows: the thickness of each layer was 0.2 mm and the printing speed was 60 mm / s.
[0049] Example 2: Preparation of bone defect repair scaffold
[0050] The method of Example 1 was referred to, except that the mass ratio of PLGA to TCP was changed from 7:3 to 6:4 in step 3 to prepare a bone defect repair scaffold.
[0051] Example 3: Preparation of bone defect repair scaffold
[0052] The method of Example 1 was referred to, except that the mass ratio of PLGA to TCP was changed from 7:3 to 5:5 in step 3 to prepare a bone defect repair scaffold.
[0053] Example 4: Preparation of anti-infection bone defect repair scaffold
[0054] The bone defect repair scaffold prepared in Example 1 was immersed in gentamicin injection (80,000 units) for 24 hours, taken out and vacuum dried, and sterilized with ethylene oxide to obtain an anti-infection bone defect repair scaffold with a gentamicin coating.
[0055] The following is the preparation method of the control sample.
[0056] Comparative Example 1:
[0057] Referring to the method of step 1 to step 4 of Example 1, the only difference is that the mass ratio of PLGA to TCP is changed from 7:3 to 4:6 in step 3 to prepare a wire. However, it is found that the obtained wire is too brittle and not suitable for FDM printing, and the bone defect repair scaffold cannot be further prepared using the FDM printer.
[0058] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0059] Experimental Example 1: Accuracy Characterization of Bone Defect Repair Scaffold
[0060] 1. Experimental methods
[0061] Test sample: the bone defect repair scaffold prepared in Example 4 of the present invention.
[0062] Experimental operation: First, take a picture of the test sample with a digital camera under natural light, and then observe it under a SEM scanning electron microscope.
[0063] 2. Experimental results
[0064] from Figure 1 It can be seen that the bone defect repair scaffold prepared by the present invention has crisscross lines and obvious pores, while the composite vancomycin / PLGA / TCP bone defect repair scaffold reported in the prior art (Chinese Journal of Aesthetic Medicine, Vol. 30, No. 5, May 2021, pp. 59-62) has mostly fused pores. Figure 2 It can be seen under an electron microscope that the pores of the bone defect repair scaffold prepared by the present invention are uniform, while the pores of the composite vancomycin / PLGA / TCP bone defect repair scaffold reported in the prior art (Chinese Journal of Aesthetic Medicine, Vol. 30, No. 5, May 2021, pp. 59-62) are of different sizes.
[0065] That is to say, compared with the composite vancomycin / PLGA / TCP bone defect repair scaffold reported in the prior art (Chinese Journal of Aesthetic Medicine, Vol. 30, No. 5, May 2021, pp. 59-62), the bone defect repair scaffold prepared in Example 4 of the present invention has higher precision.
[0066] Experimental Example 2: Biocompatibility Characterization
[0067] Test sample: the bone defect repair scaffold prepared in Example 4 of the present invention.
[0068] The scaffold was placed in a well plate, and then rabbit bone-deficient mesenchymal stem cells were dripped in and cultured for 7 days. After being fixed with formaldehyde, the scaffold was dried with gradient alcohol and observed under SEM. Figure 3 As shown, cells can be seen colonizing on the surface of the scaffold and spreading normally.
[0069] The scaffold was placed in a well plate, and mouse mesenchymal stem cells were dripped in. The scaffold was cultured for 3 days, washed twice with PBS, and then stained with a live-dead staining kit and observed under a confocal microscope. Live cells appeared green, and dead cells appeared red. Figure 4 As shown, green fluorescent cells can be seen colonizing the scaffold after staining.
[0070] The above experimental results show that the bone defect repair scaffold prepared in Example 4 of the present invention has good biocompatibility.
Claims
1. A bone defect repair material, characterized in that: It is prepared with polylactic acid-glycolic acid copolymer and calcium phosphate material as raw materials; wherein the mass ratio of the polylactic acid-glycolic acid copolymer to the calcium phosphate material is 7:3; in the polylactic acid-glycolic acid copolymer, the molar ratio of lactic acid to glycolic acid is 50:50; and the calcium phosphate material is tricalcium phosphate; The preparation method of the bone defect repair material comprises the following steps: (1) adding calcium phosphate material into organic solvent 1 and dispersing the material evenly to obtain a suspension of calcium phosphate material; (2) adding the polylactic acid-glycolic acid copolymer into the organic solvent 2 to dissolve the polylactic acid-glycolic acid copolymer to obtain a polylactic acid-glycolic acid copolymer solution; (3) mixing the calcium phosphate material suspension and the polylactic acid-co-glycolic acid solution uniformly, removing the organic solvent, and drying to obtain a composite material; (4) crushing and extruding the composite material, and collecting the wire; (5) melting the wire material at high temperature and 3D printing to obtain a bone defect repair material; In step (1), the organic solvent 1 is acetone; in step (2), the organic solvent 2 is dichloromethane or chloroform; In step (1), a dispersant is added to the organic solvent 1; the dispersant is polyethylene glycol; the mass volume ratio of the calcium phosphate material to the dispersant is 25 g:1 mL; In step (5), the parameters of the high temperature melting 3D printing include: the thickness of each layer is 0.2 mm; the printing speed is 60 mm / s.
2. A method for preparing the bone defect repair material according to claim 1, characterized in that: It includes the following steps: (1) adding calcium phosphate material into organic solvent 1 and dispersing the material evenly to obtain a suspension of calcium phosphate material; (2) adding the polylactic acid-glycolic acid copolymer into the organic solvent 2 to dissolve the polylactic acid-glycolic acid copolymer to obtain a polylactic acid-glycolic acid copolymer solution; (3) mixing the calcium phosphate material suspension and the polylactic acid-co-glycolic acid solution uniformly, removing the organic solvent, and drying to obtain a composite material; (4) crushing and extruding the composite material, and collecting the wire; (5) melting the wire material at high temperature and 3D printing to obtain a bone defect repair material; In step (1), the organic solvent 1 is acetone; in step (2), the organic solvent 2 is dichloromethane or chloroform; In step (1), a dispersant is added to the organic solvent 1; the dispersant is polyethylene glycol; the mass volume ratio of the calcium phosphate material to the dispersant is 25 g:1 mL; In step (5), the parameters of the high temperature melting 3D printing include: the thickness of each layer is 0.2 mm; The printing speed is 60mm / s.
3. An anti-infection bone defect repair material, characterized in that: The bone defect repair material is obtained by coating antibiotics on the bone defect repair material described in claim 1.
4. The anti-infective bone defect repair material according to claim 3, characterized in that: The antibiotic is an aminoglycoside antibiotic.
5. The anti-infective bone defect repair material according to claim 4, characterized in that: The antibiotic is gentamicin.
6. Use of the bone defect repair material according to claim 1 or the anti-infection bone defect repair material according to any one of claims 3 to 5 in the preparation of a bone defect repair scaffold.
Citation Information
Patent Citations
Biodegradable hard tissue repair composite scaffold prepared by 3D printing technology and preparation method thereof
CN109260522A